The ART of frozen embryo transfer: back to nature!. (2nd June 2020) - Lawrenz, Barbara; Coughlan, Carol; Melado, Laura; Fatemi, Human M.
Abstract: The implementation of cryopreservation-techniques in the IVF laboratory and the improved survival rates of oocytes, cleavage and blastocyst stage embryos have led to a significant increase in the number of frozen-thawed embryo transfer cycles (FET). FETs can be planned either in a 'pure' natural cycle, a modified natural cycle, a stimulated cycle or a hormonal replacement therapy cycle and the optimal means to prepare the endometrium for frozen embryo transfer is a topic of ongoing controversy. Recent findings report an increased risk of hypertensive disorders if pregnancy is achieved in a frozen embryo transfer cycle without an existing corpus luteum. Therefore, the question of how to prepare the endometrium has gained even more importance and taken on a new dimension as it should not simply be reduced to the basic question of 'which approach will result in superior pregnancy rates?' but instead 'which approach will result in the best pregnancy rates and the safest outcome for mother and baby?'. The aim of this review is to summarize and critically appraise the existing data on the different approaches of endometrial preparation for frozen embryo transfer with a special focus on the 'pure' natural cycle.